Trends in pacemaker mode prescription 1984-1994: a single centre study of 3710 patients. Issue 5 (May 1996) - Aggarwal, R. K.; Ray, S. G.; Connelly, D. T.; Coulshed, D. S.; Charles, R. G.
Abstract : OBJECTIVE: To evaluate trends in pacemaker mode prescription from 1984 to 1994 with particular reference to the changes in pacemaker mode prescription for patients aged 80 years and older at implant. DESIGN: Prospective evaluation of indications for pacing and pacemaker mode prescription in all patients undergoing new pacemaker implantation from 1992 to 1994. Comparison with retrospectively obtained data for patients paced from 1984 to 1991. SETTING: Tertiary referral cardiothoracic centre. PATIENTS: Group 1: 2622 patients paced at one centre and entered into the national pacing database from 1984 to 1991. Group 2: 1088 consecutive patients paced from 1992 to 1994. RESULTS: Use of atrial (AAI) and dual chamber (DDD) pacemakers increased progressively in patients of all ages from 1984 to 1994. There was an increase in the proportion of patients aged 80 years and older from 25.4% (group 1) to 40.5% (group 2). Patients of all ages in group 2 were more likely to receive DDD units for atrioventricular block (odds ratio (95% confidence interval) (CI) 9.0 (7.0 to 11.5)) and AAI or DDD units for sinus node disease (odds ratio (95% CI) 11.0 (7.7 to 15.8)) than those in group 1. Elderly patients (age > or = 80 at implant) with atrioventricular block or sinus node disease and a suitable atrial rhythm were less likely to receive DDD or AAI pacemakers than younger patients in both groups. CONCLUSIONS: Use of atrial and dual chamber pacing modes has increased substantially in patients of all ages over the last decade. Although elderly patients represent an increasing proportion of the paced population, they remain less likely to receive atrial or dual chamber pacemakers than younger patients.